Sistem Pendukung Keputusan untuk Penentuan Siswa Lulus dengan Predikat Terbaik di SMA Negeri 9 Medan Menggunakan Metode SAW - Muhammad Zidane; Elsa Aditya (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2026)
Determining the best graduating students at SMA Negeri 9 Medan has been carried out without an automated system and tends to focus more on academic aspects, potentially leading to subjectivity, inefficiency, and errors in the assessment process. Furthermore, non-academic criteria have not been optimally integrated in the decision-making process. Therefore, this study aims to design and develop a decision support system that can determine the best graduating students objectively, structured, and transparently using SAW. The SAW method is used to process student data based on a number of predetermined academic and non-academic criteria with certain weights. The system was developed using the PHP programming language with a MySQL database. The data used in this study were student assessment data at SMA Negeri 9 Medan for the 2024 academic year. The results of the system's calculations were compared with manual calculations to test the system's accuracy. The trial results showed that the implemented decision support system produced the same preference value as the manual calculation, namely 0.95 for students with the best predicate. The system's accuracy level reached 100%, indicating that the system is capable of implementing the SAW method appropriately. Thus, this system can help schools determine which students graduate with the best grades more efficiently, accurately, and responsibly.